Optimalisasi Setting Fisik untuk Mewadahi Aktivitas Interaksi Sosial pada Ruang Publik Citra Niaga - Bibiana Desy Pertiwi; Diananta Pramitasari (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Pradita, 2026)
The Citra Niaga Samarinda area is a public space located in the center of Samarinda City. The area that has received the Aga Khan Awards for Architecture has changed from time to time so that it affects the conditions of the area. The physical settings in the area cannot accommodate the user's social interaction activities by following existing needs. This study aims to determine the condition of the physical setting contained in the Citra Niaga Area which can accommodate social interaction activities. The research method is observation and place centered mapping, which aims to determine the condition of the physical setting and social interaction activities carried out in the Morning (07.00 WITA - 11.00 WITA), Afternoon (11.00 WITA - 15.00 WITA), Afternoon (15.00 WITA - 18.00 WITA), Evening (18.00 WITA - 22.00 WITA) on Weekdays (Monday - Friday) and Weekdays (Saturday and Sunday). The physical settings contained in the Citra Niaga Area are buildings, open spaces, circulation, street furniture and vegetation. The physical setting in the area is dominated by the existing physical setting with various conditions. Social interaction activities that occur in the area are in the form of active activities (traveling, playing, sports, buying and selling) and passive activities (relaxing and gathering). Social interaction activities are dominated by adolescents and adults so that when the activity is high, the physical settings in the area cannot accommodate the various social interaction activities of users.